Fenologia, banco de sementes e produção de mudas de Sideroxylon obtusifolium (Roem. & Schult.) T.D.Penn. - Cruz, Flávio Ricardo da Silva (2018)
The removal vegetation coverage stands out as one of the most serious environmental problems in different parts of the world, and in Brazil this is no exception. The Sideroxylon obtusifolium (Roem. & Schult.) T.D.Penn., belongs to the Sapotaceae Juss. Family, is an important species that is currently threatened in the Caatinga biome, which despite that fact, there is lack of studies focused in this species, especially regarding the phenology, natural regeneration and seedling production. Therefore, the objective of this study was to evaluate the different phenological stages, the soil seed bank, the influence of different substrates and shade levels on the production of S. obtusifolium seedlings. Four experiments were carried out: I - phenology: carried out in the rural area of Boa Vista - PB, with 26 individuals of the species, evaluated every 15 days for 30 months. phenological stages of budding, flowering, fruitification and senescence of the species were correlated with the climatic data of the municipality (rainfall, temperature and relative humidity); II - seed bank: carried out with two soil samples collected from the same area where the phenological evaluations were carried out, evaluating the floristic composition, density (relative and absolute), diversity of Shannon- Weaver (H ') and Pielou equability (e'); III - production of S. obtusifolium seedlings in different substrates: carried out in a protected environment of the Departamento de Fitotecnia e Ciências Ambientais do Centro de Ciências Agrárias da Universidade Federal da Paraíba (DFCA-CCA/UFPB), where were evaluated 13 substrates formulated from washed sand, bovine manure, subsoil, kaolin waste and Basaplant® (commercial substrate); IV - growth of S. obtusifolium seedlings at different levels of shade: at the forest nursery of the Laboratório de Ecologia Vegetal (CCA-UFPB), using the following shading levels: 0, 30, 50 and 70% shade. The variables evaluated in the production of seedlings were: height, stem diameter, height/stem diameter ratio, absolute height growth rate, absolute diameter growth rate, number of branches, root length, height/ root length ratio, shoot dry matter (stem, branches, leaves), root dry matter, total dry matter, shoot and root dry matter ratio (stem, branches, leaves), Dickson quality index and percentage of leaves and roots. There was no significant effect between the phenological characteristics evaluated and the environmental variables (temperature, humidity), with a strong oscillation in intensity and in the activity index. During ix the evaluation periods, senescence occurred in all individuals of S. obtusifolium. The peak of the intensity of the phenological stages of budding, floral bud, flowering and fruitification was less than 60%. In the seed bank of the studied area, 58 species were identified, distributed in 49 genera and 23 families, with predominance of herbaceous species, and belonging to the Fabaceae family. The S. obtusifolium species was not found in any of the soil samples. For the production of seedlings, kaolin waste and bovine manure are indicated, while pure subsoil associated with washed sand is not recommended. The production of seedlings of the species can be carried out under full sun or with up to 15% of shading, without significant losses in the seedlings vigor.